Antioxidant and Antibacterial Activity of The Stem Bark Extract of Sterculia Foetida L. - Theodore Yehezkiel Kristoferson Lulan; Febri Odel Nitbani; Reinner Ishaq Lerrick (Jurnal Sains dan Terapan Kimia, 2022)
Free radicals are compounds that contain one or more unpaired electrons which are very reactive, causing damage to cells or tissues and implication in the emergence of various degenerative diseases. Several methods of exploring medicinal plants have been carried out to find new sources of natural antioxidants and antibacterials that can reduce the use of synthetic drugs. This study aimed to examine the antioxidant and antibacterial activity of the stem bark extract of the plant Sterculia foetida L. The antioxidant activity of S. foetida was tested using the ABTS radical method (2,2-Azinobis 3-ethyl benzothiazoline 6-sulfonic acid). The principle of this method is that the color intensity or absorbance of the ABTS solution is inversely proportional to the concentration of antioxidant compounds. ABTS absorbance measurements were carried out at a wavelength of 734 nm. The results showed that the bark extract of the plant S. foetida could inhibit ABTS radicals with an IC50 value of 5.54 g/mL. The antibacterial activity of S. foetida was tested by measuring the optical density (OD) at a wavelength of 630 nm and expressed by the Inhibition Concentration 50 (IC50) value of 10442.29 g/mL.